Binding and effect of K(ATP) channel openers in the absence of Mg(2+) - Russ, Ulrich (2003)
1. Openers of ATP-sensitive K(+) channels (K(ATP) channels) are thought to act by enhancing the ATPase activity of sulphonylurea receptors (SURs), the regulatory channel subunits. At higher concentrations, some openers activate K(ATP) channels also in the absence of MgATP. Here, we describe binding and effect of structurally diverse openers in the absence of Mg(2+) and presence of EDTA. 2. Binding of openers to SUR2B was measured using a mutant with high affinity for [(3)H]glibenclamide ([(3)H]GBC). In the absence of Mg(2+), ‘typical' openers (benzopyrans, cyanoguanidines and aprikalim) inhibited [(3)H]GBC binding with K(i) values ∼200 × higher than in the presence of MgATP. Minoxidil sulphate and nicorandil were inactive, whereas binding of diazoxide was unaffected by MgATP. 3. In the absence/presence of MgATP, N-cyano-N′-(1,1-dimethylpropyl)-N″-3-pyridylguanidine (P1075) activated the Kir6.2/SUR2B channel in inside–out patches with EC(50)=2000/67nM and E(max)=32/134%. In the absence of Mg(2+), responses were variable with only a small part of the variability being explained by a decrease in channel responsiveness with time after patch excision and to differences in the ATP sensitivity between patches. 4. The rank order of efficacy of the openers was P1075>rilmakalim ∼nicorandil>diazoxide>minoxidil sulphate. 5. The data show that structurally diverse openers are able to bind to, and to activate the Kir6.2/SUR2B channel by a pathway independent of ATP hydrolysis. These effects are observed at concentrations used to define the biochemical mechanism of the openers in the presence of MgATP and allow the openers to be classified into ‘typical' and ‘atypical' KCOs with diazoxide standing apart.